Hacking exposed : malware and rootkits : security secrets & solutions - Davis, Michael, 1982-; Elisan, Christopher C.; Bodmer, Sean; LeMasters, Aaron (Hacking Exposed Ser., 2017)
Arm yourself for the escalating war against malware and rootkits Thwart debilitating cyber-attacks and dramatically improve your organization's security posture using the proven defense strategies in this thoroughly updated guide. Hacking Exposed"!Malware and Rootkits: Security Secrets & Solutions, Second Edition fully explains the hacker's latest methods alongside ready-to-deploy countermeasures. Discover how to block pop-up and phishing exploits, terminate embedded code, and identify and eliminate rootkits. You will get up-to-date coverage of intrusion detection, firewall, honeynet, antivirus, and anti-rootkit technology." Learn how malware infects, survives, and propagates across an enterprise " See how hackers develop malicious code and target vulnerable systems " Detect, neutralize, and remove user-mode and kernel-mode rootkits " Use hypervisors and honeypots to uncover and kill virtual rootkits " Defend against keylogging, redirect, click fraud, and identity theft " Block spear phishing, client-side, and embedded-code exploits " Effectively deploy the latest antivirus, pop-up blocker, and firewall software " Identify and stop malicious processes using IPS solutions